KONSTRUKSI “NEW EASTERN WOMEN” DALAM COVER MAJALAH HARPER’S BAZAAR INDONESIA - Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2015)
This inequalities relationship can be seen from the display cover of Harper's Bazaar magazine's Indonesian edition. Harper's Bazaar itself was an American magazine which circulates in 29 international editions in 45 negara. This research was done by analyzing cover of Bazaar Magazine Indonesia began in January 2013 - March 2014, and it used semiotic analysis of Roland Barthes. One result that stands out from this research was a practice that is done by Harper's Bazaar in preserving the dominance of Western Culture in Bazaar magazine cover that was published Indonesia. As mentioned by Lisa Cartwright, that through seeing something that a social relationship and meaning negotiated. Harper's Bazaar magazine cover to be the media to negotiate social relationships and the meaning of Indonesian women through the lens of Western culture. Through the visual appearance on the cover of the magazine, Bazaar tried to give a new meaning to the female figure Eastern Indonesia. Bring up what was referred to by Henry James as a New Woman, or more precisely New Eastern Women, as a figure of Eastern women today are ideal. A new meaning Indonesia tried to deprive women of their eastern cultural roots are sublime.